Internal medicine : tests for final knowledge control for the practical classes and individual work for 3rd year students of international faculty (speciality 221 «Dentistry») - Mykhailovska, N. S.; Grytsay, A. V.; Shershnyova, О. V.; Lisova, O. O.; Romalho Roque, T. M.; Nesterova, O. S.; Михайловська, Наталія Сергіївна; Грицай, Ганна Володимирівна; Шершньова, Оксана Володимирівна; Лісова, Оксана Олександрівна (Запорізький державний медико-фармацевтичний університет, 2023)
Tests compiled in accordance with the program of «Internal medicine (with infectious diseases, epidemiology, and clinical pharmacology)». Guidelines are intended to help students prepare for practical classes and learn the material. Can be used for training of 3rd year students of international faculty, speciality «Dentistry».